High-stress surgery in severely frail patients: a case report of personalized and multidisciplinary shared decision-making - Andrea Sanna; Sara Miori; Sergio Lassola; Michele Umbrello; Silvia De Rosa; Giacomo Bellani (Journal of Anesthesia, Analgesia and Critical Care, 2023)
Abstract We report the case of a 65-year-old severely disabled man diagnosed with advanced renal neoplasm who was scheduled for major urologic surgery. Through a multidisciplinary approach, a shared decision-making process and mutual listening of all the health professionals involved, it was decided not to have major surgery due to the high risk of worsening the patient’s health and quality of life.